TACTILE AND REFLECTIVE CONDITIONS: MARIE-JOSÉ VAN HEE’S HOUSE DECLERCQ - Fernández Contreras, Javier (Facultad de Arquitectura, Universidad Nacional Autónoma de México, 2018)
The architect Marie-José Van Hee likes to design architecture from the inside out, conceiving interior spaces with a sense of classicism in their proportions, a mastery in the use of natural light and an accomplished handling of construction techniques. Her understanding of technique is pragmatic, envisioning it not as an end in itself but as a means to an end. She enjoys the benefits of modernity without exaggerating its language. At House Declercq, her unornamented materials create the appearance of an objective architecture devoid of physical nuances, yet the texture of its solid surfaces and the landscape reflectivity of its glass point to the sensory effects of architecture.